2008
DOI: 10.1029/2008eo020001
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Ice Extent Plummets in 2007

Abstract: Arctic sea ice declined rapidly to unprecedented low extents in the summer of 2007, raising concern that the Arctic may be on the verge of a fundamental transition toward a seasonal ice cover. Arctic sea ice extent typically attains a seasonal maximum in March and minimum in September. Over the course of the modern satellite record (1979 to present), sea ice extent has declined significantly in all months, with the decline being most pronounced in September. By mid‐July 2007, it was clear that a new record low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
345
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 462 publications
(354 citation statements)
references
References 10 publications
9
345
0
Order By: Relevance
“…Maslanik et al 2007;Rothrock et al 2003), the simulated ice volume shows a considerable decline over the late twentieth to early twenty-first century in all of the CCSM3 standard runs with a corresponding reduction in the summer sea ice area. As discussed by Stroeve et al (2007), the reduction in September ice extent in these simulations is consistent with observed sea ice loss over the satellite record.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Maslanik et al 2007;Rothrock et al 2003), the simulated ice volume shows a considerable decline over the late twentieth to early twenty-first century in all of the CCSM3 standard runs with a corresponding reduction in the summer sea ice area. As discussed by Stroeve et al (2007), the reduction in September ice extent in these simulations is consistent with observed sea ice loss over the satellite record.…”
Section: Resultssupporting
confidence: 70%
“…Instead, it must be reinforced by sizable intrinsic variations in the spring and summer atmosphere and/or ocean conditions, which appear to be quite rare. This is broadly similar to conclusions on the contributing factors of the large ice loss in September of 2007 (Stroeve et al 2008;Kay et al 2008;Schweiger et al 2008;Zhang et al 2008b;Lindsay et al 2009). In particular, the adjoint analysis of Kauker et al (2009) showed that the initial (March) ice thickness in combination with May-June wind conditions, and September air temperature explained nearly 90% of the 2007 September sea ice area anomaly (Kauker et al 2009).…”
Section: Ensemble Integrationssupporting
confidence: 76%
See 2 more Smart Citations
“…Qin et al [2] studied the spatial distribution and temporal variation of snow cover in northwest China and its response to climate change. Moreover, many studies of the polar cryosphere show that Arctic sea ice has significantly declined over the past few decades [3,4], and may continue to decrease in the future. The Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment Report (AR4) models anticipate that summer sea ice in the Arctic will melt completely within 60-70 years.…”
mentioning
confidence: 99%